A novel and rapid approach to yeast differentiation using matrix-assisted laser desorption/ionisation time-of-flight mass spectrometry. Issue 1 (2003) - Sherburn Sherburn, Richard E. Richard E.; Jenkins Jenkins, Richard O. Richard O.
Abstract : Matrix-assisted laser desorption/ionisation time of flight mass spectrometry (MALDI-TOF-MS) was investigated as a method for the rapid identification of yeast cells. Following pretreatment of yeast samples with a cell wall digesting enzyme (lyticase), distinct and reproducible mass spectra over the m/z range 2, 000 to 16, 000 were obtained by MALDI-TOF-MS. Using an optimised procedure, characteristic mass spectra that distinguished between Candida spp. and between strains of Saccharomyces cerevisiae were produced. The approach offers the potential for rapid differentiation of yeasts in clinical diagnosis and in the fermentation industries.